Pengaruh Kualitas Pelayanan Dan Diferensiasi Produk Terhadap Keunggulan Bersaing Pada Nasabah Bank Sumsel Babel Syariah KCP UIN Raden Fatah Palembang - Viera Irawan; Hilda; Fakhrina (CV. ITTC INDONESIA, 2022)
Currently business competition is very competitive. Companies need a strategy to face this competition. The company must have more competitiveness compared to other companies. This competitiveness can be in the form of products produced, services or human resources. Likewise, in the world of the banking sector, especially in sharia banking, increasingly advanced technological developments have resulted in changes in customer tastes which have resulted in customers moving from one bank to another. This research aims to find out how service quality and product differentiation influence the competitive advantage of customers at Bank Sumsel Babel Syariah KCP UIN Raden Fatah Palembang. The Grand Theory of this research is to use the Resource Based View (RBV) theory. The method used is a quantitative method. The data collection technique was carried out by distributing questionnaires using a Likert scale. The sample in this study was 100 respondents with a sampling technique using Simple Random Sampling with the Slovin formula. The data analysis techniques for the questionnaire used are validity and reliability tests, classical assumption tests, multiple linear regression analysis and hypothesis testing with data processing using the SPSS ver 26 program. The research results show that the service quality variable (X1) tcount > ttable (3.428 > 1.984) has a positive and significant effect on customers' competitive advantage, so the higher the quality of service from the bank, the more customer interest there will be and can increase competitiveness. In the product differentiation variable (X2) tcount > ttable (6.318 > 1.984) has a positive and significant effect on customers' competitive advantage, so the better the bank improves the products it offers, the more superior the bank is compared to other banks. Based on the results of service quality (X1) and product differentiation (X2), they simultaneously have a positive and significant effect on the competitive advantage of customers at Bank Sumsel Babel Syariah KCP UIN Raden Fatah Palembang.